Super-paramagnetic core-shell material with tunable magnetic behavior by regulating electron transfer efficiency and structure stability of the shell - Wenyan Zhang; Jiahua Chen; Wei Wang; Lingyun Hao; Yaru Ni; Chunhua Lu; Zhongzi Xu (Results in Physics, 2016)
In this work, a spherical nano core-shell material was constructed by encapsulating Fe3O4 microsphere into conductive polymer-metal composite shell. The Fe3O4 microspheres were fabricated by assembling large amounts of Fe3O4 nano-crystals, which endowed the microspheres with super-paramagnetic property and high saturation magnetization. The polymer-metal composite shell was constructed by inserting Pt nano-particles (NPs) into the conductive polymer polypyrrole (PPy). As size and dispersion of the Pt NPs has an important influence on their surface area and surface energy, it was effective to enlarge the interface area between PPy and Pt NPs, enhance the electron transfer efficiency of PPy/Pt composite shell, and reinforced the shell’s structural stability just by tuning the size and dispersion of Pt NPs. Moreover, core-shell structure of the materials made it convenient to investigate the PPy/Pt shell’s shielding effect on the Fe3O4 core’s magnetic response to external magnetic fields. It was found that the saturation magnetization of Fe3O4/PPy/Pt core-shell material could be reduced by 20.5% by regulating the conductivity of the PPy/Pt shell. Keywords: Super-paramagnetic, Conductivity, Magnetic shielding, Structural stability